Unusual hypertrophic cardiomyopathy: case report of an early onset wild-type ATTR amyloidosis accompanied by a chromosomal duplication involving the MYH6 and MYH7 gene - Hamidi, Jassin; Hanel, Yvonne; Dittmann, Sven; Gerding, Wanda Maria; Nguyen, Huu Phuc; Klingel, Karin; Schulze-Bahr, Eric (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHypertrophic cardiomyopathy (HCM) is characterized by an increased left ventricular (LV) wall thickness and LV mass. With an estimated prevalence of 1:200–500, HCM is among the most common genetically determined cardiac diseases. Functionally, enhanced tissue stiffness and reduced elasticity, combined with diastolic dysfunction and myocardial fibrosis, can eventually lead to life-threatening arrhythmias and impaired blood flow through the heart chamber. Typical symptoms associated with HCM include atrial fibrillation (AF), syncope, ventricular fibrillation, and cardiac arrest. At the molecular level, various genetic and/or non-genetic etiologies can lead to HCM.Case summaryIn this case, we report on a 60-year-old male patient with severe, progressive hypertrophic cardiomyopathy (HCM) in an uncommon and ambivalent setting. Right ventricular (RV) biopsy and multi-phase skeletal scintigraphy diagnosed transthyretin amyloidosis with cardiac involvement. Sanger sequencing of the transthyretin gene revealed a wild-type sequence. Phenotypically, the patient initially presented with syncopal episodes, atrioventricular (AV) block, and atrial fibrillation. Subsequently, bilateral carpal tunnel syndrome and polyneuropathy developed. However, the progressive and early onset of left ventricular hypertrophy did not align with the typical presentation of HCM in the context of ATTR. Therefore, next-generation sequencing (NGS) analysis revealed a rare chromosomal duplication in both cardiac myosin genes, MYH6 and MYH7. Consequently, two distinct and rare disease entities co-occurred in this patient, both ultimately leading to HCM.DiscussionTo date, no other case featuring wild-type transthyretin amyloidosis (wtATTR) concurrently with a chromosomal duplication affecting both cardiac myosin heavy chain genes has been reported in the literature. This highlights the extreme rarity of this condition, making it challenging to ascertain the extent to which a presumably mutated hybrid myosin gene construct or the TTR amyloid fibrils contribute to stiffness, tissue fibrosis, and cardiac dysfunction. Ultimately, both effects converged in this case, leading to the same cardiac disease with an exacerbated phenotypical outcome of hypertrophic cardiomyopathy (HCM). While early onset wtATTR is an uncommon clinical finding, another significant clinical condition was identified in this patient, marked by an unusual copy number variation (CNV) in the genes MYH6 and MYH7.